2009
DOI: 10.1016/j.eneco.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oil price shocks on the Iranian economy

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
213
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(233 citation statements)
references
References 41 publications
16
213
1
3
Order By: Relevance
“…The empirical evidence reported that the relationship between oil price and GDP is non-linear and asymmetric. Farzanegan and Markwardt (2009) investigated the relationship between oil price and macroeconomic variables for Iran. Their results confirmed that a positive shock in oil price has a significant and positive impact on industrial production.…”
Section: Oil Price and Economic Growthmentioning
confidence: 99%
“…The empirical evidence reported that the relationship between oil price and GDP is non-linear and asymmetric. Farzanegan and Markwardt (2009) investigated the relationship between oil price and macroeconomic variables for Iran. Their results confirmed that a positive shock in oil price has a significant and positive impact on industrial production.…”
Section: Oil Price and Economic Growthmentioning
confidence: 99%
“…Ewing and Thompson (2007) investigate the cyclical co-movements of crude oil price with consumer prices using Hodrick-Prescott methodology. Their findings support that the price of oil is the leading factor in consumer prices in the U.S. Farzanegan and Markwardt (2009) analyze the dynamic relationship between oil price shocks and major macroeconomic variables in Iran by applying a VAR approach. They identify that negative oil price shocks significantly increase inflation.…”
Section: Previous Studiesmentioning
confidence: 70%
“…The relevant literature includes the following studies: Kahn and Hampton (1990), Huntington (1998), LeBlanc and Chinn (2004), Cunado and Perez de Gracia (2005), Ewing and Thompson (2007), Farzanegan andMarkwardt (2009), De Gregorio et al (2007), Tang et al (2010), andÁ lvarez et al (2011). These studies reveal that inflation is affected by oil price.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Farzanegan and Markwardt [9] stated that due to the high dependence on oil revenues, oil price fluctuations had a special impact on the Iranian economy. Unexpectedly, the authors noted that they could not identify a significant impact of oil price fluctuation on real government expenditures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Farzanegan and Markwardt [9] stated that due to the high dependence on oil revenues, oil price fluctuations had a special impact on the Iranian economy. By applying a VAR approach, they analyzed the dynamic relationship between asymmetric oil price shocks and major macroeconomic variables in Iran.…”
Section: Literature Reviewmentioning
confidence: 99%